An observational cohort study on 194 supraglottic cancer patients: implications for laser surgery and adjuvant treatment - Dyckhoff, Gerhard; Warta, Rolf; Herold-Mende, Christel; Rudolph, Elisabeth; Plinkert, Peter K.; Ramroth, Heribert (Cancers, 2021)
Supraglottic laryngeal cancer is characterized by poor prognosis. In contrast, excellent outcomes have been published in early-stage supraglottic cancers after laser surgery in single-institutional series in centers of excellence. Are these results reproducible in the normal clinical practice of less specialized facilities? As part of an observational cohort study, the outcomes of 194 supraglottic cancer patients were assessed after treatment by larynx-preserving surgery (transoral laser microsurgery [TLM] or open partial laryngectomy [OPL]) or total laryngectomy (TL), with each having risk-adopted adjuvant treatment, or primary (chemo-)radiotherapy (pCRT or pRT). In early-stage supraglottic cancers, TLM achieved a 5-year overall survival (5-year OS) of 62.0%. No significant survival difference could be discerned between patients with and without adjuvant treatment (HR 1.47; 95% CI: 0.80 2.69). The comparison between pCRT and pRT patients suggests that CRT is more effective in supraglottic cancer. The 5-year OS rate achieved in our multiinstitutional setting is comparable to that reached in laser surgery centers of excellence (59.4-76.0%). According to our data and supported by the literature, adjuvant RT (aRT) is not sufficiently effective in supraglottic cancers. In case adjuvant therapy is indicated, adjuvant chemoradiation (aCRT) could be recommended.
Gesehen am 04.05.2021